Fundamental Concepts for Assessment and Interpretation of Wideband Acoustic Immittance Measurements - AlMakadma, Hammam; Kei, Joseph; Yeager, David; Feeney, M. Patrick (Seminars in Hearing, 2023)
Assessment of middle ear impedance using noninvasive electroacoustic measurements has undergone successive developments since its first clinical application in the 1940s, and gained widespread adoption since the 1970s in the form of 226-Hz tympanometry, and applications in multifrequency tympanometry. More recently, wideband acoustic immittance (WAI) is allowing unprecedented assessments of the middle ear acoustic mechanics thanks to the ability to record responses over a wide range of frequencies. The purpose of this article is to present fundamental concepts for the assessment and interpretation of wideband measures, including a review of acoustic impedance and its relation to the mass, stiffness, and resistance components of the middle ear. Additionally, an understanding of the middle ear transfer function reveals the relationship between impedance and middle-ear gain as a function of frequency. Wideband power absorbance, a WAI measure, quantifies the efficiency of sound conduction through the middle ear over a wide range of frequencies, and can serve as an analogous clinical measure to the transfer function. The interpretation of absorbance measures in ears with or without a conductive condition using absorbance measured at ambient pressure and pressurized conditions (wideband tympanometry) is described using clinical case examples. This article serves as an introduction to the fundamental principles of WAI measurements.
Keywords: wideband acoustic immittance; acoustic impedance; wideband power absorbance; middle ear transfer function; resonance frequency